Determinan Pencegahan Fraud Pengadaan Barang dan Jasa pada OPD Provinsi Sumatera Selatan - Mutiara Rizki Agustina Harahap; Kartika Rachma Sari; Rosy Armaini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study was to determine the magnitude of the effect of E-Procurement Implementation, Internal Control System and Organizational Commitment on Fraud Prevention of Procurement of Goods and Services at the OPD of South Sumatra Province. Quantitative type. The population is employees at the OPD of South Sumatra Province, totaling 54 employees directly related to the PBMN of the Goods and Services Procurement Subdivision according to Perpres No. 12 of 2021. The sample amounted to 54 people with the Saturated Sampling Method. Using Primary Data collected through Questionnaires Obtained 46 Questionnaire Data can be processed with Multiple Linear Regression Analysis, using the IBM SPSS Statistics Program Version 25. The results of the research that has been carried out can be seen that Partially and Simultaneously E-Procurement Implementation, Internal Control System and Organizational Commitment have a significant positive effect on Fraud Prevention of Procurement of Goods and Services at the OPD of South Sumatra Province.